2011
DOI: 10.4236/jmmce.2011.101007
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Some Nigerian Coals as Blending Stock in Metallurgical Coke Production

Abstract: Two Nigerian coals, Lafia-Obi and Chikila were blended in the mass

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…The TPCs determined were ignition temperature (T onset ), midpoint temperature (T mid ), maximum peak decomposition temperature (T max ), burnout or offset temperature (T off ), mass loss and residual mass (R M , %). (Nasirudeen and Jauro 2011). In contrast, the ash yield of Garin Maiganga coal is significantly lower than most Polish or American coals (Nasirudeen and Jauro 2011).…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 92%
See 2 more Smart Citations
“…The TPCs determined were ignition temperature (T onset ), midpoint temperature (T mid ), maximum peak decomposition temperature (T max ), burnout or offset temperature (T off ), mass loss and residual mass (R M , %). (Nasirudeen and Jauro 2011). In contrast, the ash yield of Garin Maiganga coal is significantly lower than most Polish or American coals (Nasirudeen and Jauro 2011).…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 92%
“…The VM of the analyzed coal samples (Except for the Enugu and Imiegba coals) is considerably higher than other Nigerian coals, such as Onyeama (35 wt%), Ogwashi (27.8 wt%), Ezimo (32 wt%), Inyi (30 wt%), and Ogboyoga (30.4 wt%) (Ogala et al 2012;Sambo 2009;Sonibare et al 2010). Moreover, the VM of the analyzed coal samples except that of Enugu and Imiegba coals is significantly higher than South African coal (dry basis= 5.6 wt% and wet basis=6.3 wt%) (Akinyemi et al 2012) and Polish coals (32.61 wt%) (Nasirudeen and Jauro 2011). Conversely, the VM of the studied coals is significantly lower than Hemrin coal seam (60.58 wt%) (Kettanah and Eble 2017).…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 96%
See 1 more Smart Citation
“…The correlation study of elements in coal samples indicated that C has strong negative correlation with O, Fe, Na , S, Si and strong positive correlation with Al and Ca (r >= 0.80 ; p < 0.01) as shown in Table 5. The carbon content of a coal is essential for making mass of coke (Nasirudeen and Jauro, 2011).…”
Section: Elemental Characteristics Of Coalmentioning
confidence: 99%
“…The cupolas use foundry coke as source of fuel. There are different types of coke which includes metallurgical coke, foundry coke, formed coke, coke for electric furnaces and coke for resistor in graphitization furnaces [1][2][3][4][5][6]. All coke is made from coal but not all coals can be used to make coke.…”
Section: Introductionmentioning
confidence: 99%